An Asymmetric Iron‐Based Redox‐Active System for Electrochemical Separation of Ions in Aqueous Media. (20th February 2020) - Tan, Kai‐Jher; Su, Xiao; Hatton, T. Alan
Abstract: Electrochemically mediated redox‐active processes are gaining momentum as a promising liquid‐phase separation technology. Compared to conventional systems, they offer potential benefits, such as smaller energy footprints, nondestructive operation, reversibility, and tunability for specific analyte removal, with clear applications to societal and industrial challenges like water treatment and chemical synthesis. An asymmetric Faradaic cell heterogeneously functionalized with a metallopolymer at the anode and a hexacyanoferrate material at the cathode is presented for the first time. The redox‐active species' iron centers enhance the electrosorption of heavy metal oxyanions with up to 98% removal in the ppb range, and offer tunable operating windows as low as ≈0.1 V at ≈1 A m −2 . By avoiding water splitting, the hexacyanoferrate cathode imparts additional advantages, namely a four‐fold reduction in adsorption energy requirements, full suppression of solution pH increase, and the ability to capture redox‐active catalytic anions such as polyoxometalates without altering their bulk oxidation state. This hybrid framework of a polymeric ferrocene anode and crystalline hexacyanoferrate cathode allows for simultaneous and synergistic uptake of anions and cations, respectively, creating a new asymmetric scheme for water‐based separations, with foreseeable future extension to fields such as ion‐sensing, energy storage, and electrocatalysis. Abstract : Redox‐active materials for electrochemically mediated ion removal are emerging as a potential next‐generation technology for water remediation. An asymmetric framework combining an anodic metallopolymer and a cathodic hexacyanoferrate crystal exhibits enhanced adsorption capability for toxic heavy metal oxyanions and polyoxometalate species, with operating windows that can be tuned to as low as ≈0.1 V at ≈1 A m −2 .